Separation of Sn from waste Pb-free Sn-Ag-Cu solder in hydrochloric acid solution with ferric chloride - Lee, S.; Yoo, Kyoungkeun; Jha, M.; Lee, J. (Elsevier, 2015)
A recycling process consisting of hydrochloric acid leaching with ferric chloride as an oxidant and cementation using Sn powder followed by solvent extraction was proposed to separate Sn from Pb-free solder. Leaching tests showed that the effect of HCl concentration on the leaching efficiency of Sn was negligible in 1.0-2.0 kmol · m- 3 HCl, and the efficiency was lower at 0.5 kmol · m- 3 HCl. Higher temperature yielded higher dissolution rates of Sn and Cu in the beginning of leaching; the leaching efficiencies of Sn and Cu increased to more than 99% within 90 min, but Ag was not detected, indicating that Ag could be separated successfully from Sn and Cu. When more than 1 g of Sn powder was added to 100 ml of leach solution containing 98.1 g · m- 3 Cu, Cu ions could be removed from the leach solution by the cementation reaction. In the solvent extraction test using tri-butyl phosphate (TBP) diluted with kerosene, the extraction efficiency of Sn increased with increasing TBP volume ratio in the organic phase, and 99.9% of Sn was extracted selectively by 3-time solvent extraction with 15% TBP and 1:1 O/A ratio at 30 °C.